Implementasi ekoteologi berbasis masjid melalui gerakan 10.000 pohon sebagai model pemberdayaan pertanian berkelanjutan di Provinsi Sulawesi Selatan: Implementation of mosque-based ecotheology through the 10,000 trees program as a model for sustainable agricultural empowerment in South Sulawesi - Miftah Farid; Riavita Maghfiroh; Sri Ade Putra (Jurnal Tarreang: Tren Pengabdian Masyarakat Agrokompleks, 2026)
The issue of environmental degradation and the reduction of green open spaces in urban areas poses a significant challenge to ecosystem sustainability and community food security. One of the main causes of this is land-use change, including in mosque areas. Generally, mosque land is covered with concrete or paving to be used as parking lots, thus losing its ecological function. This condition encourages the need for an environmentally-based empowerment approach rooted in religious values. Therefore, the community service activity carried out was the Implementation of Mosque-Based Ecotheology Through the 10,000 Trees Movement as a form of ecotheology application to the community in South Sulawesi Province. The goal of this activity was to integrate Islamic teachings on nature conservation with sustainable agricultural practices by planting productive fruit trees around the mosques. The implementation method consisted of four stages: seedling and site preparation, planting, monitoring of tree growth, and evaluation of social and environmental impacts. This activity was carried out in 40 mosques with the involvement of PRIMA DMI Sulsel, the Ministry of Religious Affairs of the Republic of Indonesia, Project Dakwah, and Phinisi ID, through a series of events: the Grand Opening, Sharing Happiness, and Mosque Safari. The results of the activity demonstrated the active participation of congregations and mosque administrators, demonstrated by the involvement of 40 beneficiary mosques in the tree planting and maintenance process, as well as the willingness of mosque administrators to provide planting space and monitor seedling growth. Four productive tree species—figs, longans, breadfruit, and limes—were successfully distributed and planted at the target locations. This initiative successfully strengthened local food security and expanded the mosque's role as a centre for sustainable environmental outreach.